(untitled) (Academicia Globe: Inderscience Research, 2021)
Endurance is a quality that is hard to cultivate and easy to lose. There are several processes that take place in the body that build endurance: Endurance is the quality of physical activity, the ability of the human body to overcome fatigue in the active performance of muscle work for a long time. There are two types of durability, general and specific. General endurance is the ability of the body to overcome fatigue when any muscle is working for a long time. Specific endurance is defined as the ability to overcome fatigue when exercised over a long period of time.